Radial force control of bearingless multi-sector permanent magnet machines - Valente, Giorgio (2018)
The radial force control has been widely investigated for a variety of machine topologies aiming at the reduction of the mechanical stress on bearings as well as the overall vibration. Furthermore, it can be also applied to bearingless drives where the force control can be exploited to suspend the rotor element. Traditional radial force control techniques rely on two independent sets of windings dedicated to torque and suspension force, respectively. However, different winding structures can be employed to reduce the overall system complexity. Multiphase machines, in particular, offer the possibility to embed the radial force and torque generation in a single winding set and possess an enhanced fault tolerant capability. This thesis presents an alternative radial force and torque control technique for a multiphase sectored permanent magnet synchronous machine. The mathematical model of the machine and the theoretical investigation of the force production principle are provided. A force control methodology based on the minimization of the copper losses is described and adopted to calculate the d-q axis current references. The predicted performances of the test machine are benchmarked against finite elements analysis. An experimental rig has been manufactured in order to validate the radial force and torque control. The experimental validation focuses on the suppression of selected vibration frequencies at different speeds. The radial force control has been also exploited to levitate the rotor in order to obtain a two degrees of freedom bearingless drive. The fault tolerant capabilities have been investigated and experimentally tested considering the open-circuit of one three-phase winding. The tuning of the x-y axis position controller has been investigated and a state space approach has been followed to synthesize different position controllers.